A GALEX Far-ultraviolet Study of Dwarf Stars in Moving Groups. (7th October 2019) - Cochrane, Kevin M.; Smith, Graeme H.
Abstract: Far-ultraviolet (FUV) GALEX photometry of main-sequence stars in moving groups is used to verify that there is a relationship between age and FUV broadband magnitude among such stars. Samples of dwarf stars were compiled for twelve moving groups and a search made for both GALEX FUV magnitudes on the AB system and Johnson BV photometry. These data sets were used to calculate a (FUV −  B ) color index for each star, which in turn was plotted against B  −  V in a two-color diagram. Based on the loci that the group dwarfs define in this two-color space, there is strong evidence that among candidate members of the Hyades, HR 1614, Wolf 630, Ursa Major, Arcturus, AB Doradus, η Cephei, β Pictoris, and Tucana–Horologium moving groups there are populations of coeval stars. Evidence for coevality is weaker in the case of the ζ Herculis group, and no conclusion can be drawn for candidate stars that have previously been assigned to the Kapteyn's Star and σ Puppis groups. Polynomials of up to fifth order were fitted to the two-color loci of the dwarfs in each group. These fits were used to calculate fiducial values of (FUV −  B ) throughout a range in B  −  V color on the main sequence for most of the groups studied here. Evidence is found that at a fixed B  −  V there is a logarithmic dependence of (FUV −  B ) color on stellar age for FGK dwarfs. The relationships presented herein could potentially serve as a tool for estimating the ages of late-type Population I dwarf stars.